Is 75 Percent of Dental Caries Really Found in 25 Percent of the Population? - Mark D. Macek, DDS, DrPH; Keith E. Heller, DDS, DrPH; Robert H. Selwitz, DDS, MPH, Michael C. Manr, (Blackwell Synergy, 2004)
Dental caries prevalence is used to quantify inequalities and to target high-risk populations for interventions.